Intraclass Correlations for Evaluating the Effects of Teacher Empowerment Programs on Student Educational Outcomes. (March 2023) - Shen, Zuchao; Curran, F. Chris; You, You; Splett, Joni Williams; Zhang, Huibin
Programs that improve teaching effectiveness represent a core strategy to improve student educational outcomes and close student achievement gaps. This article compiles empirical values of intraclass correlations for designing effective and efficient experimental studies evaluating the effects of these programs. The Early Childhood Longitudinal Study, Kindergarten Class of 1998–1999 (ECLS-K) data are used to estimate empirical design parameter values in the setting of students nested within teachers nested within schools. The results show that intraclass correlations at the school level are relatively stable, and those at the teacher level increase along with grade level. We illustrate the utility of the results by demonstrating how to leverage this information to design more efficient and effective experimental studies.